Current Status and Trends of Antibacterial Resistance in China. (12th November 2018) - Hu, Fupin; Zhu, Demei; Wang, Fu; Wang, Minggui
Abstract: The bacterial resistance surveillance system is relatively well established at the national, provincial, and hospital levels in China. Two representative national surveillance networks for bacterial resistance are the China Antimicrobial Resistance Surveillance System (CARSS) and the China Antimicrobial Surveillance Network (CHINET), both established in 2005. CARSS data show the different bacterial resistance rates among different provinces and autonomous regions for each specific bacterium. CHINET data mainly represent the bacterial resistance profiles of teaching hospitals and show the changing trends of bacterial resistance in China. For clinical isolates, the ratio of gram-negative bacilli to gram-positive cocci is approximately 7 to 3. In general, gram-negative bacilli have higher antimicrobial resistance profiles in China. Regarding different bacterial species, antimicrobial resistance is multifaceted. The prevalence of extended-spectrum β-lactamases is high; Acinetobacter baumannii has a high antimicrobial resistance profile; and, notably, the prevalence of CRKP has been showing a marked increase since 2005. In addition, the prevalence of vancomycin-resistant Enterococcus is low, and the prevalence of methicillin-resistant Staphylococcus aureus and antimicrobial resistance in Pseudomonas aeruginosa showed decreasing trends from 2005 to 2017